Alfaiataria para executivos brasileiros: uma nova proposta para o clima tropical - Torres, Rachel Casarini (2015)
The garments have advanced along with the evolution of civilizations. In the history of fashion clothing had the role of protection and acceptance of the individual between social groups. In contemporary society fashion is also a key differentiator for upward mobility in the workplace, and this was the subject matter of this TCC. The research problem was the need to develop formal clothes to work, in order to provide greater thermal comfort and lightweight parts to our tropical country with high temperatures. To better fit the pieces were used the methods of tailoring and it was decided to fabrics produced in and for Brazil to better adapt the products to Brazilian environmental characteristics. The garments were developed directed to the executive public class B, introducing innovations that deliver modernity and sophistication without losing the characteristics of an outfit for work.